PENGARUH BAHAN AJAR MYOLOGI BERBASIS ANDROID UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PJKR PADA MATA KULIAH ANATOMI - Nurcholis Istiawan; Herman Kusdianto (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2018)
The use of android-based as teaching material for Myology becomes a fascinating innovation, especially for students in classroom learning, as in Anatomy subject. Mobile-learning based teaching material was supported by features of Android namely the materials, exercises, and the answer key which were interactively packaged. This study aims at investigating the effectiveness on the use of Myology android-based teaching material to enhance Physical Education students’ achievement in Anatomy subject. Quasi experimental research was used as the method by implementing pre and posttests on control and experimental classes with 30 students each class. In giving the treatment, experimental class used android based teaching material while the control class used conventional teaching materials. The data of students’ scores were analyzed using ANCOVA and the results showed that there was significant difference at .004. Therefore, null hypothesis was rejected. By then, it is concluded that Mylogy android-based teaching material was effective to be used in enhancing Physical Education students’ achievements at Anatomy subject (p<0.05).